2019
DOI: 10.18393/ejss.499122
|View full text |Cite
|
Sign up to set email alerts
|

Chemical weathering indices applied to soils developed on old lake sediments in a semi-arid region of Turkey

Abstract: Climate is a major influence on weathering processes affecting soil parent materials. Important contributors to soil formation in arid and semi-arid climatic zones are the diurnal cycles of solar heating and cooling that cause mechanical or physical disintegration of rock or parent materials, and wind-blown sands that score and abrade exposed rock surfaces. By using the Soil Taxonomy classification system, the initial aim of this study was to carry out a pedological evaluation for four soil profiles, classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
(46 reference statements)
4
13
0
1
Order By: Relevance
“…此外, 化学风化指数如Mg/Si、Ca/Si也是显著影响 新村屯洞穴微生物群落结构的重要因素. 化学风化通 常被用来衡量风化壳、土壤/古土壤和陆源碎屑沉积物 或岩石等的化学风化强度 [59] , Mg、Ca元素在风化作用 中易被溶出, 而Si则相对稳定, 因此, Mg/Si、Ca/Si比值 越大, 表明化学风化程度越剧烈 [60] . 微生物在岩石风化 以及成土作用中发挥着重要作用 [61] , 在对岩石进行风 化的过程中, 微生物分泌代谢产物如酸性物质促使矿 物分解 [62] , 或者通过电子传递对矿物中的变价元素进 行氧化/还原 .…”
Section: 环境因子对细菌群落的影响unclassified
“…此外, 化学风化指数如Mg/Si、Ca/Si也是显著影响 新村屯洞穴微生物群落结构的重要因素. 化学风化通 常被用来衡量风化壳、土壤/古土壤和陆源碎屑沉积物 或岩石等的化学风化强度 [59] , Mg、Ca元素在风化作用 中易被溶出, 而Si则相对稳定, 因此, Mg/Si、Ca/Si比值 越大, 表明化学风化程度越剧烈 [60] . 微生物在岩石风化 以及成土作用中发挥着重要作用 [61] , 在对岩石进行风 化的过程中, 微生物分泌代谢产物如酸性物质促使矿 物分解 [62] , 或者通过电子传递对矿物中的变价元素进 行氧化/还原 .…”
Section: 环境因子对细菌群落的影响unclassified
“…Compared to the soils developed from old lake sediments containing carbonates in Turkey (Özaytekin et al, 2012;Tunçay et al, 2019) and from limestones (Dengiz et al, 2013), the studied soils showed similar values of weathering indices. However, the intensity of weathering in the cross-section of soil profiles from the area of Turkey was more diverse, and the values of chemical weathering indices decreased or increased with depth.…”
Section: Discussionmentioning
confidence: 61%
“…However, the role of tors in the context of providing fresh mineral materials is still in question. In regions having a dry climate with substantial diurnal changes in temperature can cause mechanical or physical disintegration of rocks or abrasion of rock surfaces 52 , which is the case in Otago 53 . The weathering indices show that the reference sites closest to the bedrock outcrops have the lowest soil weathering degree.…”
Section: Discussionmentioning
confidence: 99%